2014
DOI: 10.5713/ajas.2014.14087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Garlic Powder on Growth, Feed Utilization and Whole Body Composition Changes in Fingerling Sterlet Sturgeon, Acipenser ruthenus

Abstract: A 12 week growth study was carried out to investigate the supplemental effects of dietary garlic powder (GP) on growth, feed utilization and whole body composition changes of fingerling sterlet sturgeon Acipenser ruthenus (averaging weight, 5.5 g). Following a 24-h fasting, 540 fish were randomly distributed to each of 18 tanks (30 fish/tank) under a semi-recirculation freshwater system. The GP of 0.5% (GP0.5), 1% (GP1), 1.5% (GP1.5), 2% (GP2) and 3% (GP3) was added to the control diet (GP0) containing 43% pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 25 publications
8
42
1
6
Order By: Relevance
“…The highest SGR was recored in the GM4 group with 4% garlic meal inclusion (1.43 ± 0.03, %/day), followed by the control group (1.38 ± 0.07, %/day), GM2 (1.27 ± 0.08, %/day) and the GM6 (1.19 ± 0.03, %/day) groups, respectively (Table 3). This growth promotion effect of diets supplemented with garlic meal can be attributed to the improved feed efficiency, which is in agreement with the results in Nile tilapia (Diab et al, 2002;Shalaby et al, 2006;Mesalhy et al, 2008;Soltan and El-Laithy, 2008;Metwally, 2009;Abdel-Hakim et al, 2010), in Asian seabass (Talpur and Ikhwanuddin, 2012), in sterlet sturgeon (Lee et al, 2014), and in Seabass fry (Saleh et al, 2015), where the incorporation of different levels of garlic increased final weights and specific growth rates of fish. Soltan and El-Laithy (2008) reported that the incorporation of 1% garlic into diets improved survival rate of Nile tilapia.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The highest SGR was recored in the GM4 group with 4% garlic meal inclusion (1.43 ± 0.03, %/day), followed by the control group (1.38 ± 0.07, %/day), GM2 (1.27 ± 0.08, %/day) and the GM6 (1.19 ± 0.03, %/day) groups, respectively (Table 3). This growth promotion effect of diets supplemented with garlic meal can be attributed to the improved feed efficiency, which is in agreement with the results in Nile tilapia (Diab et al, 2002;Shalaby et al, 2006;Mesalhy et al, 2008;Soltan and El-Laithy, 2008;Metwally, 2009;Abdel-Hakim et al, 2010), in Asian seabass (Talpur and Ikhwanuddin, 2012), in sterlet sturgeon (Lee et al, 2014), and in Seabass fry (Saleh et al, 2015), where the incorporation of different levels of garlic increased final weights and specific growth rates of fish. Soltan and El-Laithy (2008) reported that the incorporation of 1% garlic into diets improved survival rate of Nile tilapia.…”
Section: Resultssupporting
confidence: 87%
“…In contrast, Metwally (2009) who used different forms of garlic in diets for Nile tilapia fingerlings (natural garlic 40 g/kg diet, garlic oil capsules 250 mg/kg diet, and garlic powder 32g/kg diet), reported that HSI in all experimental diets with different forms of garlic decreased significantly. Similarly, Lee et al (2014) also presented significantly lower HSI in sturgeon fed diets containing garlic powder than that of fish group fed diets without garlic inclusion. …”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Recently there has been an increased interest for the application of immune stimulating function of medicinal herbs in aquaculture [6]. Various attempts has proven the positive effects of dietary medicinal plants/herbs as feed additives on growth and feed utilization in the aquaculture production of fishes and crustaceans [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%